Penerapan Gaya Desain Modern Tropical pada Perancangan Interior Terminal Kapal Pesiar dan Seaplane di Benoa, Bali - S.P. Honggowidjaja, Nathania Astria (Intra, 2014)
Indonesia is an archipelago with 33 provinces with 17,508 islands, that most of the plains are surrounded by waters. The interior design of this terminal will become a place for transportation facilities devoted to the residents who want to take advantage of cruise tourism. This project is planned as a response to the high demand of international and local tourists, which made Bali as a major tourist spot with beautiful beaches and seascape, as well as business purpose for the investor. This terminal will provoke the interest of local and international tourists, especially those using cruises and seaplane transportation to visit Indonesia. The results of this terminal design includes check-in area, baggage claim, waiting area, Departures and arrival hall, lounge, retail & duty free, cafeteria, lobby operational, office